My little pony, friendship is magic. Applejack [videorecording (DVD)] - Thiessen, Jayson; Lu, Denny (Shout! Factory Kids, 2018)
Twilight Sparkle and her friends learn about true friendship and honesty in a collection of episodes featuring Applejack.